Profile of Senile Cataract Patients at Klungkung Regional General Hospital in 2023 - Risna Dea Pramita; Ni Luh Piliantari Meigawati (Greenation Publisher & Yayasan Global Research National, 2024)
Senile cataracts are defined as cataracts that occur after age 50 due to aging. Cataract-induced blindness is preventable; however, it remains the second largest cause of blindness worldwide, following refractive disorders. This study aims to determine the profile of senile cataract patients at Klungkung Regional General Hospital in 2023. This study is a retrospective descriptive study utilizing data derived from patient medical records. A total of 2,040 visits with a diagnosis of senile cataract were obtained from 580 patients with 1,048 cataract eyes. Senile cataract patients at RSUD Klungkung are predominantly men aged 60-69 years, in an immature stage, with visual acuity <3/60. Most patients have no history of systemic comorbidities. A total of 27.1% of patients underwent surgery, 64.1% were observed, and the rest were referred due to other ocular comorbidities such as glaucoma, myopia, and retinal problems.